1990
DOI: 10.1007/bf02897230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydration on ultrafilterable platinum kinetics and kidney function in patients treated withcis-diamminedichloroplatinum(II)

Abstract: It has been reported that hypertonic saline provides protection against the renal toxicity of cisplatin (CDDP). We therefore evaluated its influence on the plasma and urinary pharmacokinetics of ultrafilterable platinum and kidney function as estimated by creatinine, inulin and PAH clearance. We undertook a randomized trial including two groups of ten patients receiving 100 mg/m2 CDDP in isotonic (group 1) or hypertonic saline (group 2) by a 20-min infusion. The hydration consisted of dextrose in group 1 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…It has been proposed that volume repletion of patients with isotonic saline protects against cisplatin-induced nephrotoxicity by flushing the cisplatin out of the body, limiting uptake into the proximal tubule cells (9). Patients treated with cisplatin are generally given up to 6 l saline/day iv (28,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that volume repletion of patients with isotonic saline protects against cisplatin-induced nephrotoxicity by flushing the cisplatin out of the body, limiting uptake into the proximal tubule cells (9). Patients treated with cisplatin are generally given up to 6 l saline/day iv (28,34).…”
Section: Discussionmentioning
confidence: 99%
“…Several theories have been proposed to explain the protective effect of hydration against cisplatin nephrotoxicity. Some investigators have suggested that hypertonic saline and saline hydration protect the kidney by increasing the rate of cisplatin excretion (9). Others have proposed that the salt provides a high concentration of chloride ions, which prevents the dissociation of the chloride ions from the platinum molecule, thereby reducing the formation of the reactive, aquated species of cisplatin (5,10).…”
mentioning
confidence: 99%
“…Patients treated with high doses of cisplatin should receive normal saline infusion (100 ml/h) prior to, during and several days following the administration of cisplatin; however, despite these measures, renal failure still occurs (Losonczy et al 2010). It has been reported that the infusion of cisplatin diluted in hypertonic saline (3%) might provide protection against the renal toxicity (Dumas et al 1990), but some studies have shown that GFR remains reduced despite this measure (Launay-Vacher et al 2008). Moreover, there is also the concern that the elevated concentration of chloride ions would prevent the formation of the aquated species responsible for the antitumor activity of cisplatin (Hanigan et al 2005).…”
Section: Current Measures Of Nephroprotection During Cisplatin Chemotmentioning
confidence: 97%
“…Thus, for a given dose, toxicity is dependent on the uptake and excretion kinetics of the drug. In this sense, several attempts have been made to improve the elimination of cisplatin in both urine (Dumas et al 1990) and bile (Basinger et al 1989), without affecting its antitumour action.…”
Section: Introductionmentioning
confidence: 99%